Development of E-Modules to Improve Scientific Explanation Ability of Students in Science Learning on Digestive System Materials - Muhammad Rojikin; Ridlo Zainur Rasyid; Supeno Supeno (SEJ (Science Education Journal), 2022)
The purpose of this research is to produce a valid, practical, and effective science e-module for the digestive system material to improve the scientific explanation skills of junior high school students. This research is development research that uses the ADDIE development model. Data collection techniques in this study include interviews, validation sheets, observation sheets on the implementation of learning, tests, and student response questionnaires. The data obtained was then analyzed to determine the validity, practicality, and effectiveness of the e-module product. The results of the research are valid, practical, and effective product development so that the product in question is feasible to use. The results of product validation show that e-modules are included in the very valid category with a validation value of 92.5%, which means their assessment is seen from two aspects, namely content validity and construct validity. This product is included in the very practical category based on its practicality value of 93.56%. This product is also included in the effective criteria, which is seen based on the test results with an n-gain value of 0.60 and the results of the student response questionnaire of 88.97%, which is included in the very good criteria. Thus, the developed e-module product can be said to be feasible to improve the scientific explanation skills of junior high school students in science learning.